The Way to a Human’s Brain Goes Through Their Stomach: Dietary Factors in Major Depressive Disorder - Aly, Janine; Engmann, Olivia (Frontiers in Neuroscience, 2020)
Globally, more than 250 million people are affected by depression (major depressive disorder, MDD), a serious and debilitating mental disorder. Currently available treatment options can have substantial side effects and take weeks to be fully effective. Therefore, it is important to find safe alternatives, which act more rapidly and in a larger number of patients. While much research on MDD focuses on chronic stress as a main risk factor, we here make a point of exploring dietary factors as a somewhat overlooked, yet highly promising approach towards novel antidepressant pathways. Deficiencies in various groups of nutrients often occur in patients with mental disorders. These include vitamins, especially members of the B-complex (B6, B9, B12). Moreover, an imbalance of fatty acids, such as omega-3 and omega-6, or an insufficient supply with minerals, including magnesium and zinc, are related to MDD. While some of them are relevant for the synthesis of monoamines, others play a crucial role in inflammation, neuroprotection and the synthesis of growth factors. Evidence suggests that when deficiencies return to normal, changes in mood and behavior can be, at least in some cases, achieved. Furthermore, supplementation with dietary factors may improve MDD symptoms even in the absence of a deficiency. Non-vital dietary factors may affect MDD symptoms as well. For instance, the most commonly consumed psychostimulant caffeine may improve behavioral and molecular markers of MDD. The molecular structure of most dietary factors is well known. Hence, dietary factors may provide important molecular tools to study and potentially help treat MDD symptoms. Within this review, we will discuss the role of dietary factors in MDD risk and symptomology, and critically discuss how they might serve as auxiliary treatments or preventative options for MDD.